A study on the impact of obsolescence on public private partnerships infrastructure projects - Mukuvari, Brighton (My University, 2020)
In 2002, South Africa embarked on type contract procurement known as the Public Private Partnership. The method of procurement was pioneered on the Inkosi Albert Luthuli Hospital in Kwazulu Natal. The government of South Africa decided to use this method of procurement on the basis that it would provide value for money on infrastructure projects to nation. PPPs were presented as the panacea to all the ills suffered during infrastructure development, lifecycle management right up to disposal. However, this has not been the case, PPP projects especially in the delivery of hospital facilities have suffered from obsolescence. The objectives of this research are to assess the current understanding of obsolescence, to compare the South African legislation to international best practice on the subject of obsolescence, to investigate the current challenges caused by obsolescence, to provide remedies that can be used to curb obsolescence in hospital PPPs. The study goes on to use the descriptive research method, however taking advantage of both quantitative and qualitative methods of data collection. The data is then presented as information in chapter four using pie charts, bar graphs, tables etc. The data is then analysed to test the hypotheses using the Chi – Square goodness of fit test. The research findings are then presented, and they include lack of political will to support PPPs by the South African government in the past 10 years and lack of skilled and honest personnel to enforce PPP legislation during the life of the hospital facility. The research goes on to conclude that there is a need for politicians to support PPPs to ensure that PPPs are successful. The research further concludes that there is also a need to train government personnel on the management and enforcement of PPP legislation to ensure concessions stick to the agreed deliverables in terms of hospital infrastructure management. Penultimately, the research recommends that there be contractual flexibility for PPPs to also take into consideration unknowns that arise during the contract period. Lastly, it is important to carry out and complete this study as the subject of obsolescence in PPP projects especially in hospitals is still in its infancy within the South African context
A research report submitted in partial fulfilment of the requirements of the MSc in Building in the field of Project Management in Construction (by Coursework and Research Report), for the Faculty of Engineering and the Built Environment, University of the Witwatersrand, 2020
Keywords: Public-private sector cooperation-South Africa; Public contracts